Pengaruh Social Media Marketing dan Electronic Word Of Mouth (E-WOM) Credibility Terhadap Perilaku Pembelian Konsumen Pada Produk Kopi Good Day - Ni’matul Rizky; Mukhroji, S.E., M.M (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Digitalization has changed the way customers collect data and make purchasing decisions. This study investigates how social media marketing and electronic word-of-mouth (e-WOM) credibility influence Good Day Coffee consumers' purchasing behavior. One hundred carefully selected individuals participated in this quantitative study. Data were assessed for validity and reliability after being collected through a questionnaire and then analyzed using multiple linear regression. The results indicate that e-WOM credibility has a positive but not statistically significant effect on purchasing behavior, while social media marketing has a positive and significant effect. The findings suggest that social media marketing plays a more significant role in driving purchasing behavior than other factors. Therefore, companies need to optimize their social media marketing strategies by presenting relevant and engaging content and collecting positive reviews to build customer trust and ultimately drive sales.